Rational design strategies for electron-deficient semiconducting polymers in ambipolar/n-channel organic transistors and all-polymer solar cells. Issue 39 (24th September 2018) - Wang, Yang; Michinobu, Tsuyoshi
Abstract : This review has critically summarized the recent molecular design strategies for the electron-deficient semiconducting polymers. The molecular structural implications related to the ambipolar/n-type device performances of transistors and all-polymer solar cells are discussed. Abstract : The past two decades have witnessed significant progress in the field of organic electronics, especially polymer thin-film transistors (PTFTs) and polymer solar cells (PSCs), which provide a promising opportunity for applications in flexible and wearable devices. Thanks to the efforts of the rapid development of p-type semiconducting polymeric materials and device optimization, an impressive hole mobility over 10 cm 2 V −1 s −1 and power conversion efficiency near 15% have been achieved in PTFTs and PSCs, respectively. However, the development of electron deficient semiconducting polymers for ambipolar/n-type PTFTs and polymer donor–polymer acceptor type PSCs (all-PSCs) lags far behind. Therefore, the design and synthesis of new electron-deficient semiconducting polymers have attracted increasing attention during the past five years. This review attempts to critically summarize the recent molecular design strategies with respect to the electron-deficient semiconducting polymers. These polymers have demonstrated interesting electronic properties and promising performances as active layers in ambipolar/n-type PTFTs and all-PSCs. The molecular structural implications related to the ambipolar/n-type device performances of the PTFTs and all-PSCs are discussed.